Heterogeneous interactions in online community : economic and social impact for online sellers - Chen, Yi (2019)
Despite that the interactions in online communities are diverse and differ in their content, the impact of these different interactions has received little attention. With data collected from both an online forum and an ecommerce platform, the dissertation explores the heterogeneity of online interactions in the ecommerce sellers’ online community. Drawing on the social exchange theory, while using machine learning techniques to differentiate individuals’ interactions in the online forum, we identify three types of resource exchanged in the online sellers’ community: instrumental support, informational support, and emotional support. We conduct two studies to examine how the interactions of exchanging these heterogeneous types of support might impact the sellers’ economic outcomes and social outcomes. The first study examines the economic impact of receiving and providing each type of support. The findings demonstrate that receiving instrumental support, providing instrumental support, and receiving informational support in the online community are positively associated with the sellers’ sales performance on the ecommerce platform. However, a seller’s interactions that exchange emotional support or provide informational support are not associated with the sellers’ sales performance. The second study explores how a seller’s contribution of different types of support in the online community will trigger others’ reciprocity, reflected by the responses the seller’s threads receive. The findings reveal that a seller’s provision of informational support is positively associated with the responses the seller’s threads receive, while a seller’s provision of instrumental support is negatively associated with the responses the seller’s threads receive. Moreover, the effect is moderated by the types of support sought by that particular thread.